2021
DOI: 10.1021/acscatal.1c01148
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium(II)-Catalyzed Regioselective 1,2-Hydrosilylation of N-Heteroarenes and Tetrel Bonding Mechanism

Abstract: An efficient regioselective dearomatization of N-heteroarenes using a ruthenium precatalyst [Ru-(p-cymene)(PCy 3 )Cl 2 ] 1 is achieved. Reactions were performed under mild and neat conditions. A wide variety of N-heteroarenes undergo the addition of silanes in the presence of precatalyst 1, leading to exclusive N-silyl-1,2-dihydroheteroarene products. This catalytic method displays a broad substrate scope; quinolines, isoquinolines, benzimidazoles, quinoxalines, pyrazines, pyrimidines, and pyridines undergo hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 71 publications
1
25
0
Order By: Relevance
“…While in the unfavorable 2,1-insertion transition state TS5-2 , such two interactions disappear and two distinct noncovalent interactions (CH···O and OH···π) are found. Such a kind of O···C noncovalent interaction between the hydroxyl oxygen and carbonyl carbon has been observed in previous research, which is found to promote reaction selectivity …”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…While in the unfavorable 2,1-insertion transition state TS5-2 , such two interactions disappear and two distinct noncovalent interactions (CH···O and OH···π) are found. Such a kind of O···C noncovalent interaction between the hydroxyl oxygen and carbonyl carbon has been observed in previous research, which is found to promote reaction selectivity …”
Section: Resultssupporting
confidence: 64%
“…Further examining the structures of the preferable transition states, TS5-1 (Figure S4), a newly identified O···C tetrel bonding between alkynyl hydroxyl oxygen and carbonyl carbon is found. Tetrel bonding is regarded as a kind of powerful noncovalent interaction between electron donors and the group 14 elements of the periodic table, which is a significantly important interaction in metal complex catalysis . The O···C distance is calculated to be 2.96 Å.…”
Section: Resultsmentioning
confidence: 99%
“…The metal-catalyzed hydrosilylation of N-heteroarene with phenylsilane gave the mono- and bis-1,2-hydrosilylation derivatives. Unfortunately, none of the previous reports revealed the mechanism for the formation of bis-1,2-hydrosilylation derivatives.…”
Section: Resultsmentioning
confidence: 97%
“…As far as 1,2-selective hydrosilylation of Nheteroarenes is concerned, only a few reports are known, including transition-metal and main-group metal catalysts. 18−22 The research groups of Chang, 18 Gunanathan, 19 Harder, 20 Nikonov, 21 and Yao 22 independently reported Ir, Ru, Ca, and Zn metal-catalyzed 1,2-selective hydrosilylation of N-heteroarenes, respectively (Scheme 1b).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Expanding to N -heterocycles, the groups of Suresh and Guananathan reported the ruthenium catalysed 1,2-hydrosilylation of N -heteroarenes (Scheme 24), using [Ru-( p -cymene)(PCy 3 )Cl 2 ] as the precatalyst. 70 In contrast to previous hydrosilylations of N -heteroarenes with calcium, 71 iridium 72 and zinc, 73 this is exclusively regioselective. The N -heteroarene substrate scope included quinolines, isoquinolines, benzimidazoles, quinoxalines, acridines, pyridines, pyrazines and pyrimidines.…”
Section: Catalytic Synthesis Of N-silylaminesmentioning
confidence: 88%